(untitled) (International Journal of Engineering Materials and Manufacture, 2023)
The persistent struggle against cancer has given rise to the development of nanotheranostics, a domain that integrates therapeutic and diagnostic capabilities within nanoscale structures. This paper explores advancements in nanomaterials and nanoparticles for cancer nanotheranostics, focusing on their design, significance, and applications. The incorporation of biocompatible nanoparticles in cancer therapy offers personalised, targeted approaches while minimising side effects. The use of nanomaterials such as metals, polymers, and lipids enable precise drug delivery and imaging. Various imaging modalities, including ultrasound and fluorescence, complement therapeutic strategies for enhanced precision. Critical parameters for nanomaterial selection and design are discussed, emphasising biocompatibility, targeting efficiency, and drug delivery capacity. Biocompatibility ensures safe interactions within biological systems, requiring mitigation of toxicological concerns through strategies like anti-inflammatory peptides or ligand-functionalization. Targeting efficiency combines passive and active targeting to enhance specificity, reshaping cancer diagnostics and therapy. Drug delivery capacity is achieved through engineered core-shell structures with distinct properties, including liposomes, micelles, and dendrimers, each tailored for targeted therapy and imaging. This paper also discusses the advancements in the field of cancer treatment using nanotheranostics and its economic impact on the Canadian healthcare systems while following the ethical guidelines towards patients’ consent, privacy, and the proper use of emerging technologies.